(untitled) (Revista Argentina de Musicología, 2024)
This article aims to analyze indexicality and iconicity in sounds and music from a socio-semiotic perspective. The proposed level of inquiry is the pre-semiological one, which focuses, among others, on the substances of expression. In order to understand the physical nature of these substances, the device through which each of them has been generated should be considered; this device will in turn determine its semiotic status, in terms of the categories of Peirce’s second trichotomy (icons, indexes and symbols). Among the different types of sounds, the work addresses direct natural sounds, mediatized sounds, synthesis sounds and sampled sounds, as they work on electronic instruments. Towards the end, some examples are presented, in order to show the kind of analysis that could be made about musical works adopting an approach such as the one proposed.